Synthesis of a Fragment of Crystalline Silicon: Poly(Cyclosilane). (29th November 2016) - Press, Eric M.; Marro, Eric A.; Surampudi, Sravan K.; Siegler, Maxime A.; Tang, Joel A.; Klausen, Rebekka S.
Abstract: We report a strategic synthesis of poly(cyclosilane), a well‐defined polymer inspired by crystalline silicon. The synthetic strategy relies on the design of a functionalized cyclohexasilane monomer for transition‐metal‐promoted dehydrocoupling polymerization. Our approach takes advantage of the dual function of the phenylsilyl group, which serves a crucial role both in the synthesis of a novel α, ω‐oligosilanyl dianion and as a latent electrophile. We show that the cyclohexasilane monomer prefers a chair conformation. The monomer design ensures enhanced reactivity in transition‐metal‐promoted dehydrocoupling polymerization relative to secondary silanes, such as methylphenylsilane. Comprehensive NMR spectroscopy yields a detailed picture of the polymer end‐group structure and microstructure. Poly(cyclosilane) has red‐shifted optical absorbance relative to the monomer. We synthesize a σ–π hybrid donor–acceptor polymer by catalytic hydrosilylation.